Long-Term River Water Quality Trends in Five Turkish Basins (1997–2015): CCME-WQI, OWQI, and Non-Parametric Analysis - Kartal, Veysi; Akiner, Muhammet Ernur; Yavuz, Veysel Süleyman; Karakoyun, Erkan; Bilgin, Ayla; El-Zahab, Samer (Springer Science and Business Media Deutschland GmbH, 2026)
Water quality represents a critical environmental, sociological, and economic concern in many regions worldwide. Consequently, the sustainable management of water resources has become an increasingly vital issue. This study evaluates long-term trends in river water quality across five major Turkish basins—Kızılırmak, Yeşilırmak, Sakarya, Konya, and the Eastern Black Sea—using data from 1997 to 2015. A dataset comprising monthly measurements of 26 physico-chemical parameters was analyzed with non-parametric tests (Mann–Kendall, Sen’s slope) and two composite indices: the Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) and the Oregon Water Quality Index (OWQI). Results show that 42% of parameter–station combinations exhibited significant monotonic trends, with nutrients (NO₃-N, PO₄-P) generally increasing and salinity-related variables (EC, Na⁺, Cl⁻) declining in several basins. CCME-WQI values ranged from “poor” to “good,” with temporal improvement observed in the Kızılırmak and Sakarya basins, while OWQI classifications corroborated moderate to poor water quality in agriculturally influenced regions. Mining and agricultural activities were identified as key drivers of spatial variation, particularly in Konya and Yeşilırmak. These findings highlight persistent water quality pressures in central and northwestern Türkiye, underscoring the need for targeted basin-scale management and integrated monitoring strategies. © The Author(s), under exclusive licence to Shiraz University 2026.
Keywords: Ccme-Wqi; Mann–Kendall; Multivariate Analysis; Owqi; River Water Quality; Sen Slope; Surface Water Management; Trend Analysis; Water Pollution